he jurisdiction of the state consultative council and its role in protecting the public rights and freedoms - يونس, مها بهجت; جمعة, جهاد علي (Journal of Legal Sciences, 2019)
The State Legislative Council practices its Judgement specialization through issuing the judicial decisions in combats that present to it and the judicial commissions take charge of this mission inside the council and they are the High Administrative Court, the Administrative Judgement Court and the Employees Judgement Court.Where the High Administrative Court specializes in presented appeals against the decisions of the Administrative Judgement Court and Employees Judgement Court whereas the Administrative Judgement Court in the validity of the administrative decisions issued by the employees and the general commissions whereas  the Employees Judgement Court specializes in the employees appeals against the decisions of breaching the discipline punishments and in the cases created by applying the civilian service Law or any other service laws.The State Legislative Council through its Advisory specialization could protect the rights and general freedoms where it contributed in protecting the personal freedom through issuing the decisions that cancel the administrative decisions about sequestering individuals without Judgement Decision and the compensation instead of the damages they caused and also protecting the right of travel through cancelling the decisions that restrict this right, the council contributed in protecting the rights and intellectual freedoms through its tendency to cancel the administration decisions that restrict the freedom of publishing and media and those which restrict the right of education.The council had a role of protecting the rights and economic freedoms through issuing the decisions that cancel the administration decisions that attack the special property and also cancelling the administrative decisions that restrict the trade freedom.The council contributed in protecting the rights and social freedoms through issuing the decisions that protect the work right and the Social Insurance.